2023
DOI: 10.1177/14644207231174325
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic auxetic structure with fixed Poisson's ratio for piezo-resistive strain sensor to detect human body motion

Abstract: Auxetic materials have different types whose mechanical behaviors are different from each other, and these differences affect their sensitivity. However, in the piezo-resistive strain sensor field, less attention has been paid to this variety of structures. In this article, the isotropic auxetic structure with three axes of symmetry was used to construct the isotropic linear piezo-resistive strain sensor. Structures that have only three or six symmetry axes have isotropic mechanical behavior, and structures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Reproduced with permission. 230 Copyright 2023 SAGE Publications (f ) Schematic structure of flexible piezoresistive sensors. (g) Photograph of an as-assembled PDMS/CB sensor and (h) schematic illustration of sensing mechanisms of piezoresistive sensor with vertical electrode design.…”
Section: Working Mechanismmentioning
confidence: 99%
“…Reproduced with permission. 230 Copyright 2023 SAGE Publications (f ) Schematic structure of flexible piezoresistive sensors. (g) Photograph of an as-assembled PDMS/CB sensor and (h) schematic illustration of sensing mechanisms of piezoresistive sensor with vertical electrode design.…”
Section: Working Mechanismmentioning
confidence: 99%
“…However, using the auxetic structure to regulate the performance of strain sensor was reported by several papers in the past few years. [23][24][25]27,28,47,57,58,[61][62][63][64][65][66][67] In this article, the optimization was such that by changing the geometry of the sensor structure, its sensing performance was improved. It means that a connection was established between the mechanical properties and the sensory properties of the sensor, and this type of optimization had not been done in the literature review.…”
Section: Parameters Affecting the Auxetic Sensor Sensitivity And Line...mentioning
confidence: 99%
“…In the previous part, an important feature of the sensor (linearity) was discussed, and in this part, another feature (excellent sensory performance) will be discussed. Figure 13 shows the schematic comparison of the sensitivity of the presented sensor with the previous sensors including conventional sandwich, [7] auxetic sandwich, [24] auxetic mixed, [23] and isotropic linear auxetic mixed [28] sensors in terms of mean, median, and standard deviation. As shown in Figure 13, the presented sensor has a significantly better performance compared to the previous sensors.…”
Section: Sensitivity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the importance of changing the structure and the importance of using the core-shell idea, a comparison between the re-entrant, [8] constant Poisson's ratio (CPR), [17] and planar isotropic [31] auxetic sensors with the same condition (including materials and manufacturing methods) showed that the sensory performance of the sensor will change by changing the structure. Figure 1 shows the Poisson's ratio (PR) (a) and the sensitivity (b) in terms of the strain for the three mentioned sensors.…”
Section: Introductionmentioning
confidence: 99%